A CONCEPTUAL STUDY ON SOCIAL MEDIA EFFECTIVENESS OF ADVERTISING IN COSMETIC INDUSTRY - Aina Faqihah Amir; Rusnifaezah Musa (International Journal of Accounting, Finance and Business, 2024)
In today’s world, social media is not just a convenience, it is a lifeline connecting us with loved ones and shaping our choices, even influencing what we buy. While online shopping brings ease, it also sparks skepticism. Shockingly, many companies miss the mark on honesty in their ads, forgetting that not everything on social media is as real as it seems. The study employs a quantitative research design to investigate the impact of social media advertising effectiveness on purchase intentions for beauty and cosmetic products in Malaysia. The research framework is based on the Theory of Planned Behavior (TPB), emphasizing the crucial role of an individual’s intention to engage in a particular behavior as the main predictor of whether they will do it. The study aims to gather data from a target population of online cosmetics buyers, utilizing an online survey distributed across various social media platforms. The survey instrument employs a five-point Likert scale to assess respondents' perspectives on relevant constructs. The study will involve a sample of 300 Malaysian individuals who actively use various social media platforms to purchase online cosmetics. Data analysis techniques include descriptive statistics, correlation analysis, and multiple linear regressions using the Statistical Package for Social Science (SPSS) software. The study will test hypotheses by examining the relationships between independent variables such as trust, credibility, attractiveness, and authenticity, and their impact on purchase intention. The findings of this study will provide valuable insights into the evolving landscape of social media and its impact on consumer behavior, particularly in the context of online shopping.